The challenge of antimicrobial glazed ceramic surfaces. Issue 6 (15th March 2022) - Reinosa, J.J.; Enríquez, E.; Fuertes, V.; Liu, S.; Menéndez, J.; Fernández, J.F.
Abstract: The resistance that microorganisms develop to antibiotics is a worldwide challenge. The antimicrobial agents as disinfectants for surface treatments are widespreadly used to prevent the proliferation of microorganisms, but their use should be repeated over time to ensure a complete microbe-free surface. Surfaces with permanent antimicrobial properties suppose a recent demand in materials science for functional polymeric coatings, metals, treated wood or ceramic glazed tiles. Whereas polymeric coating has been extensively studied, the antimicrobial functionality on ceramic glazed surfaces is not completely achieved. This work reviews glazed ceramic tiles developments in antimicrobial and virucidal surfaces. The main antimicrobial physical or chemical mechanisms have been described as the base to develop active glazed surfaces. The main tests required to evaluate the antimicrobial response in glazed ceramic tiles are also summarized. The high temperature required in the ceramic processing is the key point to achieve a micro/nanostructure that potentiates the antimicrobial and virucidal response of the glazed surfaces. A discussion on recent developments as well as the main routes and challenges to obtain permanent surfaces with antimicrobial and virucidal response is provided.